Glucose and the Injured Brain-Monitored in the Neurointensive Care Unit - Rostami, Elham (Frontiers in Neurology, 2014)
Brain has a continuous demand for energy that is met by oxidative metabolism of oxygen and glucose. This demand is compromised in the injured brain and if the inadequate supply persists it will lead to permanent tissue damage. Zero values of cerebral glucose have been associated with infarction and poor neurological outcome. Furthermore, hyperglycemia is common in patients with neurological insults and associated with poor outcome. Intensive insulin therapy to control blood glucose has been suggested and used in neurointensive care with conflicting results. This review covers the studies reporting on monitoring of cerebral glucose with microdialysis in patients with traumatic brain injury (TBI), subarachnoid hemorrhage (SAH) and ischemic stroke. Studies investigating Intensive insulin therapy are also discussed. Available data suggests that low cerebral glucose in patients with TBI and SAH provides valuable information on development of secondary ischemia and has been correlated with worse outcome. There is also indication that the location of the catheter is important for correlation between plasma and brain glucose. In conclusion considering catheter location, monitoring of brain glucose in the neurointensive care not only provides information on imminent secondary ischemia it also reveals the effect of peripheral treatment on the injured brain.